Solitary Intracranial Plasmacytoma in an Unusual Location – A Case Report - Bishokarma, Suresh; Shrestha, Shikher; Ranabhat, Kajan; Panth, Rajesh (Nepal Journal of Neuroscience, 2019)
Plasmacytoma is rare form of plasma cell dyscrasias, where there is malignant proliferation of plasma cells. Solitary plasmacytoma developsin isolation without systemic manifestations of multiple myeloma (MM). We report a case of cerebellopontine angle (CPA) plasma cytoma, which masqueraded as a schwannoma with multiple cranial nerve involvement and review a literature pertaining to the same pathological entity.